COGNITIVE STRATEGIES OF S²R MODEL USED BY HIGH PROFICIENCY LEARNERS OF THE ENGLISH DEPARTMENT, PETRA CHRISTIAN UNIVERSITY - Mega Sri Yunita Samalaty; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2017)
This is a qualitative and quantitative study on cognitive strategies of S²R model and specific techniques employed by high proficient learners of the English Department, Petra Christian University. The high proficient learners represented by nine final-year students who have an average of very good grade (≥B+) in all language skill courses offered by the department. The data was taken by conducting interviews to each of learners based on Oxford (2011) theory. The findings showed all types of cognitive strategies are used by the high proficient learners. The highest percentage of cognitive strategies used was going beyond the immediate data (100%), the second highest was using senses to understand and remember (81%), the third highest was conceptualizing broadly (78%), then it followed by conceptualizing with details (76%), reasoning (67%), and activating knowledge (56%). Moreover, there were a lot of varieties of the specific techniques employed by the participants. The most common specific techniques used were guessing, watching English speaking films, skimming, comparing English to mother tongue, reading novels and magazine, and brainstorming. In conclusion, all proficiency learners use all cognitive strategies but they might employ different techniques in their learning process.